Genotype‐phenotype relationships in the low‐phospholipid‐associated cholelithiasis syndrome: A study of 156 consecutive patients. Issue 3 (29th July 2013) - Poupon, Raoul; Rosmorduc, Olivier; Boëlle, Pierre Yves; Chrétien, Yves; Corpechot, Christophe; Chazouillères, Olivier; Housset, Chantal; Barbu, Véronique
<x xml:space="preserve">Abstract</x> The low‐phospholipid‐associated cholelithiasis syndrome (LPAC; OMIM 171060) is a peculiar form of intrahepatic cholelithiasis occurring in young adults, associated with ABCB4/MDR3 gene sequence variations. Our aim was to determine the genotype‐phenotype relationships in 156 consecutive patients with the criteria of LPAC syndrome. A variant was detected in 79 (61 missense and 18 truncating sequence variants), 63 being monoallelic. The clinical features (age at onset, high prevalence in women, frequency and severity of acute and chronic complications, intrahepatic cholestasis of pregnancy [ICP]) were similar in the patients with or without ABCB4 gene sequence variation. Truncating variations were associated with an earlier onset of symptoms both in women and men. Acute and chronic biliary complications were variant‐independent. Half of the women who had pregnancy developed ICP. The frequency of ICP and fetal complications were similar in patients with missense and truncating variants. Conclusion: The LPAC syndrome is more frequent in women and highly associated with ICP. Half of the patients harbored missense or truncating variants of the ABCB4 gene. The characteristics of the patients without detectable variant are similar to those with variant, indicating that yet unexplored regions of the ABCB4 and other genes may be involved. (Hepatology 2013;53:1105–1110)